PENGARUH KUALITAS PELAYANAN AKADEMIK, BIAYA PENDIDIKAN DAN LINGKUNGAN SEKOLAH TERHADAP KEPUASAN SISWA DI SMK PGRI 1 SEMARANG - Alicia Anggraini; Agung Kuswantoro (Jurnal Manajemen Pendidikan, 2026)
This study was conducted to analyze the influence of academic service quality, tuition fees, and the school environment on student satisfaction at SMK PGRI 1 Semarang. The study employed a quantitative approach using an associative method to determine the relationships and influences among the research variables. The population in this study consisted of 340 students at SMK PGRI 1 Semarang, comprising students in grades 10, 11, and 12. The sample was determined using the Slovin formula with a 5% margin of error. As a result, a sample of 184 respondents was selected using proportional random sampling. This study involved several stages, including the development of research instruments, data collection conducted through observation, documentation, and the distribution of questionnaires using a Likert scale, followed by data processing and analysis. The data analysis techniques used included validity testing, reliability testing, descriptive statistical analysis, classical assumption testing, multiple linear regression analysis, hypothesis testing (t-test and F-test), and the coefficient of determination (R²) using IBM SPSS Statistics 25. The results of the study indicate that the quality of academic services, tuition fees, and the school environment have a positive and significant effect on student satisfaction, both individually and collectively. The significance value for the academic service quality variable is 0.001, for tuition costs 0.000, and for the school environment 0.000.